Beneficial Effects of Physical Activity in Diabetic Patients - Cannata, Francesca; Vadalà, Gianluca; Russo, Fabrizio; Papalia, Rocco; Napoli, Nicola; Pozzilli, Paolo (Journal of functional morphology and kinesiology, 2020)
One of the main goals of diabetic therapy is to achieve the best metabolic control to prevent the development and progression of potential complications. A multidisciplinary approach characterized by the combination of diet, physical activity (PA) and drug therapy with oral and injectable (non-insulin) pharmacological agents, is desirable to optimize metabolic control. The aim of this review is to explain the contribution of PA and its beneficial effects on patients affected by type 1 (T1D) and type 2 diabetes (T2D). We provide an overview of evidence on the effects of PA for the main two types of diabetes mellitus (DM) to identify the right level of PA to be recommended. We discuss the physiological and clinical role of PA in people with DM. It can be concluded that the objective of antidiabetic therapy should be the achievement and optimization of metabolic control through a multidisciplinary approach involving non-pharmacological therapy such as diet and PA, which has a crucial role.